A design of expert-based development and optimization of voriconazole-loaded aspasomal gel for topical delivery - Shubham Bajirao Patil, Panchakshari Dandagi, Sujay Hulyalkar, Rubeen Dadakalandar Nadaf (Journal of Applied Pharmaceutical Science, 2024)
The research aimed to develop a voriconazole (VRC)-loaded aspasomal gel for topical drug delivery, to minimize the dosing frequency and associated side effects. Aspasomal formulations were prepared using the thin film hydration method and their vesicle size (VS) and entrapment efficiency (%EE) were assessed. Optimization was carried out using a 32-factorial design by design expert software. The optimized batch underwent in vitro anti-fungal activity testing and morphological analysis using high-resolution transmission electron microscopy. This optimized batch was then incorporated into a gel, and various parameters such as drug content, pH, viscosity, spreadability, in vitro diffusion, ex vivo permeation, and in vivo skin irritancy were evaluated. The optimized aspasomal formulation displayed a VS of 171.36 ± 2.3 nm and an %EE of 80.77% ± 1.75%. In vitro drug diffusion and ex vivo permeation studies demonstrated significant release rates of 94.09% and 48.87% after 24 and 12 hours, respectively. The optimized formulation exhibited better in vitro anti-fungal activity against Candida albicans compared to a commercially available formulation. Skin irritancy tests on rat skin showed no signs of erythema or edema, confirming non-irritation. Long-term stability analysis confirmed the formulation’s stability under cold conditions. In conclusion, VRC-loaded aspasomes present a promising alternative for treating skin fungal infections, offering controlled drug release and minimizing adverse effects, ultimately enhancing patient outcomes.
Keywords: Voriconazole, aspasomes, topical delivery, optimization, anti-fungal study